Phase 3, Randomized, Double-blind Noninferiority (NI) Study of Ceftazidime–Avibactam (CAZ-AVI) vs. Meropenem (MER) in the Treatment of Patients with Hospital-acquired Bacterial Pneumonia and Ventilator-associated Bacterial Pneumonia (HABP/VABP): Analyses of the REPROVE Study per US FDA Endpoints. (4th October 2017) - Torres, Antoni; Rank, Doug; Rekeda, Ludmyla; Chen, Xiang; Riccobene, Todd; Critchley, Ian; Lakkis, Hassan; Melnick, David; Chow, Joseph W; Taylor, Dianna; Laud, Peter J; Talley, Angela K
Abstract: Background: HABP/VABP due to Gram-negative (GN) pathogens is associated with significant mortality and treatment options are limited. The Phase 3 REPROVE study (NCT01808092) demonstrated the efficacy and safety of CAZ-AVI vs. MER in the treatment of patients with HABP/VABP, including patients with ceftazidime-nonsusceptible (CAZ-NS) pathogens as per the EMA-mandated analysis plan (Torres et al. 2017). Data are presented here for the 2014 US FDA guidance-specified endpoints and analysis populations. Methods: Adult patients with HABP or VABP were randomized 1:1 to receive CAZ-AVI 2.5 g IV q8h or MER 1 g IV q8h for 7–14 days. The primary objective was to demonstrate NI of CAZ-AVI to MER with respect to all-cause mortality at Day 28 in the intent-to-treat (ITT) population, based on a 10% NI margin. Key secondary endpoints included the clinical cure at test of cure (TOC) in the ITT and microbiological-ITT (micro-ITT) populations. Results: 879 patients were randomized in 23 countries; 99% received treatment (436 CAZ-AVI and 434 MER = ITT population); 44.4% of patients were ventilated at baseline; the mean APACHE II score was 14.8. 43.5% of patients had a GN pathogen isolated at baseline (micro-ITT population). The predominant GN baseline pathogens were K. pneumoniae (36.6%) and P. aeruginosa (30.1%); 28.3% of patients had infections due to CAZ-NS pathogens. CAZ-AVI was noninferior to MER with respect to all-cause mortality at Day 28 (CAZ-AVI 9.6% vs.. MER 8.3%; difference 1.5%; 95% CI: -2.4, 5.3) and with respect to the clinical cure at TOC (CAZ-AVI 67.2% vs.. MER 69.1%; difference -1.9%; 95% CI: -8.1, 4.3). Results in the micro-ITT population were consistent with these analyses, as were results for the subgroups of patients with VABP, non-VABP, CAZ-NS baseline pathogens, renal impairment, and augmented renal clearance. The incidence and type of adverse events was balanced between treatment groups and consistent with the established safety profiles for both drugs. Conclusion: This is the first successful Phase 3 HABP/VABP study based on the 2014 FDA Guidance. CAZ-AVI is effective and well-tolerated in the treatment of adult patients with HABP/VABP, including those with infections due to CAZ-NS pathogens. Disclosures: A. Torres, AstraZeneca: Investigator, Consulting fee; D. Rank, Allergan plc: Employee, Salary; L. Rekeda, Allergan plc: Employee, Salary; X. Chen, Allergan plc: Employee, Salary; T. Riccobene, Allergan plc: Employee, Salary; I. Critchley, Allergan plc: Employee, Salary; H. Lakkis, Allergan plc: Employee, Salary; D. Melnick, Allergan plc: Employee, Salary; J. W. Chow, Astrazeneca: Employee, Salary; D. Taylor, Astrazeneca: Shareholder, Stock; P. J. Laud, Astrazeneca: Consultant, Consulting fee; A. K. Talley, Allergan plc: Employee, Salary